Grassland diversity in the Mediterranean zone of Chile is greatly affected by land use system and grazing intensity - Del Pozo A.; Ovalle C.; Casado M.A.; Acosta B.; De Miguel J.M. (Sustainable Mediterranean grasslands and their multi-functions, 2008)
The anthropogenic savannas (Espinales) represent the most widespread agro-ecosystem of the Mediterranean area of central Chile. It presents a complex and heterogeneous, savannas-like structure, with herbaceous and woody strata. The intensive land use of the Espinales has reduced the woody cover (mainly Acacia caven) affecting the herbaceous vegetation. Grassland communities were studied in 29 plots of 1000 m2, with a wide range of woody cover and geomorphologic situations. The effect of grazing intensity was studied in a long-term experiment of seven stocking rate treatments (1 to 4 sheep ha/year). At any woody cover, grasslands were dominated by grasses followed by composites. The relative abundance of legumes was very low. The relationship between woody cover and grassland diversity (Shannon index) was unimodal in flatland areas. Grazing intensification had large effects on the structure of grassland. As grazing intensity increased grassland diversity decreased; composites became the predominant family in detriment of grasses. Legumes were usually scarce and were not affected by grazing intensity. The overgrazed community allows higher native species richness than exotic ones, possibly due to the greater defence traits against herbivores of this group of species.
12. Meeting of the Sub-Network on Mediterranean Forage Resources of the FAO-CIHEAM Inter-regional Cooperative Research and Development Network on Pastures and Fodder Crop, 2008/04/09-12, Elvas (Portugal)